Efforts to Improve Students' Learning Engagement in Science Learning Using the Teams Games Tournament (TGT) Model in Grade VIII of SMPN 22 Padang - Salsabila Ismail; Widia Kemala Sari (Global READ Center, 2026)
This study was conducted to address the low level of students’ learning engagement in science learning at Grade VIII.G of SMP Negeri 22 Padang. The study aimed to improve students’ learning engagement through the implementation of the Teams Games Tournament (TGT) cooperative learning model. This study employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, which consisted of two cycles: planning, action, observation, and reflection, involving 32 students of Grade VIII.G. Data were collected using observation sheets and learning engagement questionnaires and analyzed descriptively using percentage analysis. The study was considered successful when students’ learning engagement reached at least the Active category based on the predetermined success criteria. The findings showed that students’ learning engagement improved throughout the research cycles. The average questionnaire score increased from 58.7% in the pre-cycle to 74.5% in Cycle I and 79.0% in Cycle II, while the average observation score increased from 53.5% to 69.9% and 78.1%, respectively. These findings suggest that the implementation of the Teams Games Tournament (TGT) cooperative learning model improved students’ learning engagement in science learning among the participants involved in this study.